Identification of leukemic and pre-leukemic stem cells by clonal tracking from single-cell transcriptomics - Velten, Lars; Story, Benjamin A.; Hernández-Malmierca, Pablo; Raffel, Simon; Leonce, Daniel R.; Milbank, Jennifer; Paulsen, Malte; Demir, Aykut; Szu-Tu, Chelsea; Frömel, Robert; Lutz, Christoph; Nowak, Daniel; et al. (Nature Communications, 2021)
Cancer stem cells drive disease progression and relapse in many types of cancer. Despite this, a thorough characterization of these cells remains elusive and with it the ability to eradicate cancer at its source. In acute myeloid leukemia (AML), leukemic stem cells (LSCs) underlie mortality but are difficult to isolate due to their low abundance and high similarity to healthy hematopoietic stem cells (HSCs). Here, we demonstrate that LSCs, HSCs, and pre-leukemic stem cells can be identified and molecularly profiled by combining single-cell transcriptomics with lineage tracing using both nuclear and mitochondrial somatic variants. While mutational status discriminates between healthy and cancerous cells, gene expression distinguishes stem cells and progenitor cell populations. Our approach enables the identification of LSC-specific gene expression programs and the characterization of differentiation blocks induced by leukemic mutations. Taken together, we demonstrate the power of single-cell multi-omic approaches in characterizing cancer stem cells.
Gesehen am 12.05.2021